Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fmicb.2021.664339
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Expression of Cyclodextrin Glycosyltransferase my20 in Escherichia coli and Its Application in 2-O-α-D-Glucopyranosyl-L-Ascorbic Acid Production

Abstract: In this study, the cgt gene my20, which encodes cyclodextrin glycosyltransferase (CGTase) and was obtained by the metagenome sequencing of marine microorganisms from the Mariana Trench, was codon optimized and connected to pET-24a for heterologous expression in Escherichia coli BL21(DE3). Through shaking flask fermentation, the optimized condition for recombinant CGTase expression was identified as 20°C for 18 h with 0.4 mM of isopropyl β-D-L-thiogalactopyranoside. The recombinant CGTase was purified by Ni2+-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The purified CGTase exhibited optimum activity at pH 5 and 95 °C, thermostability even at 100 °C, and converted starch to β-CD majorly [20]. Song et al [54] reported the cloning of codon-optimized CGTase encoding gene (my20) procured from the metagenome sequencing of marine microorganisms (obtained from Mariana Trench) in a pET24a vector and its subsequent expression in E. coli BL21 (DE3). Recombinant CGTase was maximally expressed at 20 °C after 18 h postinduction by using 0.4 mM IPTG, with the enzyme exhibiting optimal activity at pH 7 and 80 °C [54].…”
Section: Production and Properties Of Cgtasementioning
confidence: 99%
See 1 more Smart Citation
“…The purified CGTase exhibited optimum activity at pH 5 and 95 °C, thermostability even at 100 °C, and converted starch to β-CD majorly [20]. Song et al [54] reported the cloning of codon-optimized CGTase encoding gene (my20) procured from the metagenome sequencing of marine microorganisms (obtained from Mariana Trench) in a pET24a vector and its subsequent expression in E. coli BL21 (DE3). Recombinant CGTase was maximally expressed at 20 °C after 18 h postinduction by using 0.4 mM IPTG, with the enzyme exhibiting optimal activity at pH 7 and 80 °C [54].…”
Section: Production and Properties Of Cgtasementioning
confidence: 99%
“…For example, CGTase from Thermoanaerobacter thermosulfurigenes EM1 has a temperature optimum of 80-85 °C [92], CGTase from Thermoanaerobacter sp. has a temperature optimum of 80 °C [54], and CGTase from Bacillus stearothermophilus NO2 has an optimum enzyme activity at 70 °C [84]. Moreover, recombinant CGTase from Pyrococcus furiosus DSM3638 expressed in E. coli exhibited a temperature optimum of 95 °C [20].…”
Section: Production and Properties Of Cgtasementioning
confidence: 99%